Sea level variability in the Tropical Atlantic since 1993 and projections to 2100 - Ghomsi, Kemgang Franck Eitel (Department of Oceanography, 2025)
Global Mean Sea Level (GMSL) is a critical climate metric that captures the cumulative effects of thermal expansion, changes in ocean mass and ice melt. Understanding GMSL is essential for coastal adaptation strategies, but regional variations can differ significantly from the global average, complicating local response efforts. This thesis deals with the implications of GMSL variations for the African coast, focusing on the GoG, the ETAO, and southern Africa. Employing an integrated approach combining satellite altimetry, tide gauges, GRACE/GRACE-FO gravimetric data, hydrographic profiles, and CMIP6 multi-model ensemble simulations, with time-series analysis and wave propagation studies, the research quantifies sea level trends, steric and mass components, and wave dynamics over 1993–2022, with projections to 2100. The thesis synthesising the results of four different studies to provide a comprehensive perspective on sea-level rise (SLR) and its impacts on these vulnerable coastal areas. The GoG, spanning from Liberia to Gabon, faces heightened vulnerability to coastal flooding exacerbated by both local and climate-induced sea-level rise. Analysis of nearly three decades of satellite altimetry data from 1993 to 2021 reveals a significant increase in the rate of mean sea level rise, from 3.47 to 3.89 ± 0.10 mm/yr, accompanied by an acceleration of 0.094 ± 0.050 mm/yr². This increase corresponds to a cumulative sea level rise of about 8.9 cm over the study period. The study highlights the influence of extreme warm and cold events, such as Atlantic Niños and Benguela Niños, driven by remote equatorial Kelvin waves (EKW) and local factors such as wind and freshwater fluxes. Analysis of coastal trapped Kelvin waves (CTWs) in the GoG in relation to major warming events in 2010, 2012, 2019 and 2021 shows a significant one-month lag between EKWs and West African CTWs. This observation is crucial for improving predictions and managing the impacts of extreme events on local ecosystems, fisheries, and socio-economic activities. In the ETAO, spanning from 1993 to 2022, the study examines spatio-temporal trends in sea level anomalies (SLA) and their components thermosteric, halosteric, and ocean mass. The regional SLA trend of 3.52 ± 0.47 mm/yr aligns closely with the global average of 3.56 ± 0.67 mm/yr, with the GoG exhibiting a slightly lower regional trend of 3.42 ± 0.12 mm/yr. Our study underscores the dominance of the ocean mass component in long-term trends, supported by GRACE and GRACE-FO missions, which indicate a total SLR of 3.80 ± 0.8 mm/yr, with a residual increase in the ETAO of 3.69 ± 0.5 mm/yr. We also found strong correlations with regional climate factors, particularly the Tropical South Atlantic Index, highlighting the need for targeted adaptation strategies for densely populated coastal communities. Projections for the GoG indicate a severe risk of coastal inundation by 2100, with potential inundated areas ranging from 1,458.1 km² to 4,331.7 km² under low and high- emission scenarios, respectively. By comparing projections from eight CMIP6 models with historical sea surface height data and current topography, the study confirms that the one-month lag in CTW propagation will persist. The potential inundation could displace up to 2 million people, significantly impacting local economies and cultural heritage. This underscores the urgent need for robust adaptation strategies and early warning systems, aligned with the UN's Sustainable Development Goals (SDGs), particularly SDG 13 (Climate Action) and SDG 14 (Life Below Water). In southern Africa, the research reveals that sea level rise in coastal areas such as Cape Town is nearly double the global average, reaching 6.3 mm/yr. Coupled with subsidence rates exceeding 2.2 mm/yr, this poses a severe threat to communities, infrastructure, and ecosystems. The study also examines the impact of seismic activity on subsidence, providing a nuanced understanding of the interplay between natural and anthropogenic factors. These findings highlight the urgent need for proactive coastal management and adaptation strategies to safeguard both communities and cultural heritage sites. Overall, this thesis offers a comprehensive understanding of the impacts of sea-level rise along the African coast, highlighting the need for localised adaptation strategies and informed decision-making. By integrating satellite altimetry, GRACE data and CMIP6 climate model projections, the research provides valuable insights into the challenges posed by sea-level rise. This study contributes significantly to understanding regional sea level variability, offering essential knowledge for developing effective coastal management policies in response to ongoing and projected sea level changes. It emphasizes the importance of continued research to support resilient coastal management in the face of climate change.